Implementasi Enterprise Risk Management pada Proyek-Proyek Strategis Daerah oleh Inspektorat Daerah Kota Blitar - Indarti, Ratih Dewi; Arisyahidin, Arisyahidin (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The government's internal oversight apparatus has a strategic role in supporting and strengthening the effectiveness of the internal control system in order to ensure effective, efficient, and accountable governance. Blitar District Inspectorate, in its role as Quality Assurance, is able to bring the Government of Blitar to the Warrant Opinion Without Exclusion (WTP) for 13 consecutive times from BPK RI on inspection of the Financial Report of the Regional Government (LKPD). However, in the implementation of the duties and maintenance of the government, there are still findings and recommendations of the results of inspection from BPC RI as well as BPKP and other APIPs that are included in the Examination Results Report. This descriptive qualitative research was conducted aimed at studying the implementation of enterprise risk management in the Blitar District Inspectorate and conducting an analysis of the factors that are inhibiting the supervision of the inspectorate as an APIP in order to strengthen the control of the risk of fraud on strategic projects in Blitar City. The results of the research showed that the Inspectorates of Blitar Region Inspection have implemented Enterprise Risk Management (ERM) in the supervision of the strategic project of the City of Blitar in five (5) aspects of the ERM. Nevertheless, based on the observation data, interviews, and documentation, there are still challenges faced by the Blutar District Inspection in its task of supervising and managing the risk of the strategic projects of the city of Blitar.